An organic approach to sustainability (Mayéutica Revista Científica de Humanidades y Artes, 2021)
The organic as an agricultural practice, transcends the mere productive fact due to its implications, since it is based on agroecological principles closely linked to sustainability. Within the market economies of developed countries, consumer segments are increasingly demanding products that come from nonpolluting production processes and require governments, the promotion of nature protection measures, through the application of friendly practices, identified with the elimination of chemical inputs and attached to the organic, or from a broader conception, to the agroecological. In this way, by assuming the latter as an alternative that is opposed to conventional treatment, the preservation of biodiversity is advocated and its condition as an indispensable factor for our future existence is exalted. The achievement of the full realization of the human condition, and therefore of human development, requires identifying in all areas, the existence of interrelationships and interdependencies that must be strengthened for our own survival as living beings, in conjunction with those who make up and share the planet.
Keywords: sustainability; human development; biodiversity; organic practices